2009
DOI: 10.1007/s00415-009-5117-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of leukocyte adhesion molecules in patients after ischemic stroke

Abstract: Leukocyte recruitment and inflammatory response play an important patho-physiologic role after cerebral ischemia. This study aimed to evaluate whether leukocyte adhesion molecules can predict clinical outcome in patients after ischemic stroke. We prospectively examined serial changes in p-selectin glycoprotein ligand-1 (PSGL-1), macrophage antigen-1 (Mac-1), and lymphocyte function-associated antigen-1 (LFA-1) expression by leukocyte subsets using flow cytometry at various time points in 65 acute ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…In addition to NIHSS scores, there are several clinical risk factors that contribute to poor functional outcomes after ischemic stroke [8,[13][14][15][16][17][18][19]. The majority of the damage following acute ischemic stroke does not occur immediately, but rather develops gradually over the course of the following hours [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to NIHSS scores, there are several clinical risk factors that contribute to poor functional outcomes after ischemic stroke [8,[13][14][15][16][17][18][19]. The majority of the damage following acute ischemic stroke does not occur immediately, but rather develops gradually over the course of the following hours [20].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke severity was assessed with the NIHSS. Early neurologic deterioration (END) was defined as an increase of four points in the NIHSS score between admission and any time during the first 48 hours of hospitalization [8]. The Outpatient Department followed most surviving patients after discharge, although some were interviewed by telephone, to identify neurological outcomes.…”
Section: Clinical Data Collectionmentioning
confidence: 99%
“…CR3 is expressed in myeloid cells, notably neutrophil granulocytes and macrophage subsets, with major roles in leukocyte extravasation and phagocytosis (3). CR3 contributes to atherosclerosis (4), and the severity of acute ischemic stroke correlates with the level of CR3 expressed on monocytes (5). Inhibition of CR3 expressed in microglial cells limits synaptic loss in animal models of Alzheimer disease (6).…”
mentioning
confidence: 99%
“…den Hertog et al [3] studied the relation between CRP values and poor outcome (mRS [ 2) or death at 3 months in 561 patients within 12 h of ischemic stroke onset that participated in the Paracetamol (Acetaminophen) In Stroke (PAIS) trial. Patients with CRP levels C7 mg/L more often had a poor outcome (57 vs. 42%; p = 0.006) or died (23 vs. 13%; p = 0.0007) than patients with lower CRP levels.…”
Section: Biomarkers: Understanding the Pathophysiology Of Ischemiamentioning
confidence: 99%
“…Tsai et al [2] evaluated the value of leukocyte adhesion molecules in 65 acute ischemic stroke patients and 60 controls, showing that the expression of leukocyte adhesion molecules on admission is significantly increased in patients with acute ischemic stroke. This prospective study found that higher neutrophil PSGL-1 expression on day 1 is associated with a higher risk for early neurologic deterioration (END) and that monocyte Mac-1 expression reflects the severity of ischemic stroke.…”
Section: Biomarkers: Understanding the Pathophysiology Of Ischemiamentioning
confidence: 99%